Description of Schendylops jeekeli sp. n., a new geophilomorph centipede (Myriapoda: Chilopoda) from the Paranapiacaba fragment of the Atlantic Forest in Southeastern Brazil, with complementary notes on similar Neotropical species - Pereira, Luis Alberto (2009)
Schendylops jeekeli sp. n. (Chilopoda: Geophilomorpha: Schendylidae) is here described and illustrated on the basis of a male specimen collected in Alto da Serra of Paranapiacaba (State of São Paulo, Southeastern Brazil Region) in a remnant fragment of the Atlantic Forest. Th is new species is characterized by having ventral pore fields on the anterior region of the body only, and is compared in detail with those Neotropical members of the genus sharing the same trait and having a similar range of leg-bearing segments. It is also included in a key which is provided for identifi cation of all the species of Schendylops from the Neotropics with a similar feature. Further morphological data and new illustrations for S. interfluvius (Pereira, 1984), S. paolettii (Pereira & Minelli, 1993) and S. schubarti Pereira, Foddai & Minelli, 2002 are given on the basis of re-examination of type materials.